THE SECRETS OF UNICORN COMPANIES: AN EMPIRICAL INVESTIGATION - Ioana MEȘTER; Darie GAVRILUȚ (Annals of the University of Oradea: Economic Science)
Starting a new business is a challenging task, and many factors can affect the success or failure of the venture. One such factor is the field of activity in which the business operates. Some industries are more competitive than others, and some have more significant barriers to entry. This article aims to explore the influence of the field of activity on the survival and growth of new businesses. The startup ecosystem has been on the rise in recent years, with the emergence of several unicorns, or startups valued at over $1 billion. This has led to increased interest in entrepreneurship and the potential for significant financial returns. However, the reality is that most startups do not become unicorns, and many do not survive beyond a few years. The field of activity in which a startup operates can significantly influence its survival and growth prospects. Several studies have explored the influence of the field of activity on the survival and growth of new businesses. These studies have found that factors such as competition, regulatory compliance, access to financing, and availability of talent can significantly influence a startup's chances of survival and growth. For example, industries with high levels of competition and technological intensity have been found to have lower rates of new firm survival and growth (Carrie, et al., 2002). This study investigates a possible correlation between several statistical dimensions of unicorn start-up companies in the world. For this purpose, we will use descriptive as well as inferential statistical methods such as presenting the main parameters of the numerical variables, some graphical representations; we will also employ a nonparametric correlation analysis. We consider that there is a possible correlation between the date the companies were set up, their field of activity, country of origin and their valuation respectively. Our study confirmed four research hypotheses, as follows: there is a correlation between the date the unicorn start-up companies were set up and their valuation, their valuation and their field of activity, the field of activity is in statistical association with the companies country of origin and the field of activity is influenced by the date the companies were set up. We will conclude by discussing the implications of these findings for entrepreneurs, policymakers, and investors, and provide recommendations for improving the survival and growth prospects of new businesses.